Copyright and art work in South Africa - Johannes, Louise Renee (My University, 2011)
It is in the nature and tradition of artists to use the works and ideas of other artists within the context of their own work. Artists find copyright law restrictive and experience difficulty in determining where to draw the line between using other artistic works as inspiration and exploiting the skill and labour of others. In addition, the maxim that there is no copyright in ideas, only in the expression of ideas, is not as simple as it appears. This report is aimed at assisting the visual artist in aspects of copyright law, specifically in relation to the distinction between ideas and the expression of ideas in a material form. The method used in the research is an analysis of South African legislation and cases that illustrate the law in relation to ideas and the expression of ideas in an artistic work. As a result of the dearth of case law and literature in South Africa dealing with copyright and visual art, reference is made to American case law and the defence of fair use of an artistic work, with reference to artist Jeff Koons. The findings of the study are that the South African Courts are not in favour of allowing artists to monopolise ideas or combinations of ideas and the definitive threshold of originality is low. To constitute an infringement of an artistic work it is the artistic features or attributes of the work that have to be transformed or adapted, not some concept, that it conveys. An artist is therefore free to use the ideas of other artists, provided that such ideas are expressed in a material form and they do not form a substantial part of the work of another.